2021
DOI: 10.3934/neuroscience.2021030
|View full text |Cite
|
Sign up to set email alerts
|

Potential molecular link between the β-amyloid precursor protein (APP) and hypoxanthine-guanine phosphoribosyltransferase (HGprt) enzyme in Lesch-Nyhan disease and cancer

Abstract: <abstract> <p>Lesch-Nyhan disease (LND) is a rare X-linked inherited neurogenetic disorders of purine metabolic in which the cytoplasmic enzyme, hypoxanthine-guanine phosphoribosyltransferase (HGprt) is defective. Despite having been characterized over 60 years ago, however, up to now, there is no satisfactory explanation of how deficits in enzyme HGprt can lead to LND with the development of the persistent and severe self-injurious behavior. Recently, a role for epistasis between the mutated hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Another member of this family, amyloid precursor protein, encoded by APP , was previously reported to be a clinically significant and prognostic factor in AML1-ETO cases [ 44 ]. Moreover, APP and APP-like protein-2 ( APLP2 ) are deregulated in cancer cells and linked to increased tumor cell proliferation, migration, and invasion [ 45 ]. NPM1 represents the most frequently mutated gene in AML, is known as a good prognostic marker, and thus might be of potential clinical significance and targeted therapy [ 46 ] in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Another member of this family, amyloid precursor protein, encoded by APP , was previously reported to be a clinically significant and prognostic factor in AML1-ETO cases [ 44 ]. Moreover, APP and APP-like protein-2 ( APLP2 ) are deregulated in cancer cells and linked to increased tumor cell proliferation, migration, and invasion [ 45 ]. NPM1 represents the most frequently mutated gene in AML, is known as a good prognostic marker, and thus might be of potential clinical significance and targeted therapy [ 46 ] in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Other relevant transcriptional alterations were involved in energy metabolism [ 74 ], cell differentiation and maturation [ 77 ], cAMP/PKA signaling [ 78 ], cell cycle and division, nucleic acid metabolism [ 75 ], and purinergic signaling [ 79 ]. Nguyen [ 80 ] has suggested that epistasis between mutated HPRT1 and amyloid precursor protein ( APP ) genes may affect the APP splicing, producing alternative APP fragments that might be responsible for the neurobehavioral syndrome.…”
Section: Hypoxanthine-guanine Phosphoribosyltransferasementioning
confidence: 99%
“…Hypoxanthine guanine phosphoribosyltransferase 1 (HPRT1) is a rate-limiting enzyme in the DNA salvage pathway, whose activity is critical to maintaining the purine pool and promoting cell cycle progression through the regulation of guanine and inosine production [ 3 , 4 ]. Although it is broadly regarded as a housekeeping gene, recent studies have demonstrated the differential expression level of HPRT1 between malignant and normal tissues, implying that it may play functional roles in tumorigenesis and is unreliable as an endogenous control in cancer-related studies [ [5] , [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%